Building Safer Workplaces: Unveiling the Impact of Safety Leadership Styles in the Construction Industry - S. Senthamizh Sankar; K. S. Anandh (Administrative Sciences)
This study investigates the most effective leadership style for enhancing safety performance in the construction industry. Through a scientometric analysis of 114 research papers and a meta-analysis of 13 studies involving 7220 participants, it uncovers a growing body of research on safety leadership in construction and identifies safety-specific transformational leadership as the most impactful style for improving safety outcomes. The research highlights the increasing importance of safety leadership in the construction sector and reveals a trend towards safety-specific transformational leadership as the preferred approach. This leadership style emphasizes empowering and motivating employees to prioritize safety through shared values, vision, and goals. The study also emphasizes the need for enhanced collaboration among researchers and institutions, and advocates for the inclusion of studies from developing countries to ensure a comprehensive understanding of safety leadership practices globally. Additionally, the findings align with the Sustainable Development Goals 3, 8, and 11, underscoring the significance of fostering safe and secure working environments and promoting sustainable urbanization. This research serves as a valuable resource for construction industry stakeholders seeking to implement effective safety leadership strategies, and it lays the groundwork for further exploration in this critical area.